Interaktives Gebäude-Energiemanagement - Becker, Birger (KIT Scientific Publishing, 2014)
In this work the Energy Management Panel is presented, which is a comprehensive application for the interaction between the user and the Building Energy Management. The Building Manager extends a specific Building Energy Management System to integrate user interaction. The result of coupling these two components is the Interactive Building Energy Management, which combines three essential elements: Visualization, Parameterization and System Configuration.